COMMUNAL TOLERANCE AND THE POLITICS OF NON-MUSLIM HOUSES OF WORSHIP IN CILEGON, INDONESIA EXTENDING JEREMY MENCHIK’S THEORY OF COMMUNAL TOLERANCE - Ismail; Hamdani; Arif Zamhari; Muhammad Adlin Sila; Harapandi Dahri (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2026)
This study examines the social dynamics and institutional barriers involved in establishing non-Muslim houses of worship in Cilegon City, Banten Province, Indonesia. Unlike prior case studies that rely primarily on legal-administrative analysis, this research combines legal and sociocultural approaches to examine how formal regulation, collective social memory, and local politics interact to shape religious tolerance in a Muslim-majority city. Using an intrinsic case study design, data were collected from 15 purposively sampled informants through in-depth interviews, field observation, and document review conducted between March 2022 and December 2024, with analysis completed by July 2025; data were analyzed thematically. The findings identify three interrelated factors that sustain the absence of permanent non-Muslim houses of worship: (1) the historical narrative of the 1888 Geger Cilegon uprising, which continues to shape perceptions of religious exclusivity; (2) a widely shared, undocumented narrative of an institutional agreement between PT Krakatau Steel and local Islamic leaders that is treated as a moral constraint on religious zoning; and (3) limited public understanding of Joint Ministerial Regulation (PBM) No. 9 and 8 of 2006, which is interpreted through social and moral frameworks rather than administrative procedure. Together, these factors sustain a negotiated arrangement — termed here adaptive tolerance — in which minority worship is informally accommodated while remaining symbolically restricted. Conceptually, this study extends Jeremy Menchik’s theory of communal tolerance by showing how historical and bureaucratic memory, rather than interreligious solidarity alone, structures the boundaries of tolerance. The findings inform two policy directions: (1) participatory, village- and sub-district-based socialization of PBM regulations, and (2) the development of standardized mediation protocols within the Forum for Religious Harmony (FKUB) to strengthen inclusive religious coexistence. Abstrak Penelitian ini mengkaji dinamika sosial dan hambatan kelembagaan dalam proses pendirian rumah ibadah non-Muslim di Kota Cilegon, Banten. Berbeda dengan studi kasus sejenis yang umumnya menggunakan pendekatan hukum administratif, penelitian ini memadukan pendekatan hukum dan sosiokultural untuk mengkaji bagaimana regulasi formal, memori sosial kolektif, dan politik lokal saling berinteraksi dalam membentuk toleransi beragama di kota yang mayoritas penduduknya beragama Islam. Dengan desain studi kasus intrinsik, data dikumpulkan dari 15 informan yang dipilih secara purposif melalui wawancara mendalam, observasi lapangan, dan telaah dokumen yang dilaksanakan pada Maret 2022–Desember 2024, dan analisis data diselesaikan pada Juli 2025; data dianalisis secara tematik. Hasil penelitian mengidentifikasi tiga faktor yang saling terkait dan mempertahankan ketiadaan rumah ibadah non-Muslim permanen: (1) narasi historis peristiwa Geger Cilegon 1888 yang terus membentuk persepsi eksklusivitas keagamaan; (2) narasi yang diyakini luas namun tidak terdokumentasi mengenai perjanjian kelembagaan antara PT Krakatau Steel dan tokoh Islam setempat, yang diperlakukan sebagai batasan moral atas zonasi keagamaan; dan (3) lemahnya pemahaman publik terhadap Peraturan Bersama Menteri (PBM) No. 9 dan 8 Tahun 2006, yang dimaknai melalui kerangka sosial dan moral, bukan prosedur administratif. Ketiga faktor ini bersama-sama mempertahankan sebuah pengaturan yang dinegosiasikan — disebut di sini sebagai toleransi adaptif — yang mengakomodasi ibadah minoritas secara informal namun tetap membatasinya secara simbolik. Secara konseptual, penelitian ini memperluas teori toleransi komunal Jeremy Menchik dengan menunjukkan bahwa memori historis dan birokratis, selain solidaritas antarumat beragama, turut membentuk batas-batas toleransi. Temuan ini berimplikasi pada dua arah kebijakan: (1) sosialisasi PBM yang partisipatif berbasis desa/kelurahan, dan (2) pengembangan protokol mediasi yang terstandardisasi dalam Forum Kerukunan Umat Beragama (FKUB) guna memperkuat koeksistensi keagamaan yang inklusif.